Assessment of spring maize genotypes under rainfed and irrigated conditions in mid-hills of far-west Nepal - Sandesh Thapa; Sara Rawal; Biraj Poudel; Bronika Thapa; Neha Rai; Archana Bhatt (Discover Agriculture)
Abstract Rainfall is vital for determining crop growth factor and yield in areas where irrigation facility is limited and a major part of maize area in Nepal is under rainfed system. This experiment was conducted to identify superior yielding genotypes with higher grain yield and yield governing traits with respect to prevailing scenario under rainfed and irrigated cropping system. The experiment was conducted from first may, 2022 to 26th august, 2022 in RCBD design with nine genotypes and three replications under both irrigated and rainfed conditions. Among the tested genotypes, maximum plant height was reported in genotype Deuti and Manakamana-3 in irrigated and rainfed condition, respectively. Days to anthesis and silking were earlier in sano ghogha in both condition and minimum anthesis silking interval was reported in Deuti followed by Kanchan 101 and Thulo ghogha in both conditions. Cob characteristics varied significantly except NOGPR across environments and the highest hundred kernel weight was reported in Thulo ghogha in both conditions. Correlation analysis revealed that grain yield shows a positive correlation with cob-characteristics showing considerable increase in yield with increase in cob-traits. The highest grain yield was reported in Bisco (11.6t/ha) and Kanchan 101 (9.6 t/ha) in irrigated condition, and in rainfed condition highest yield was reported in Godavari (9.06t/ha), Kanchan 101 (8.93 t/ha) and Bisco gold (7.9t/ha). Thus, Kanchan 101 and Bisco gold 941 should be further evaluated in response to other agronomic practices and adopted for commercial cultivation in mid-hill rainfed areas.